Promotional effect of NH3 on mercury removal over biochar thorough chlorine functional group transformation. (1st June 2020) - Zhang, Huicong; Wang, Tao; Zhang, Yongsheng; Sun, Baomin; Pan, Wei-Ping
Abstract: The mercury removal performance of chlorine plasma-modified biochar was tested under NH3 and NH3 combined with a NO/SO2 atmosphere. The addition of NH3 promotes the mercury removal process of modified biochar, and the mercury removal efficiency can be increased by up to 17.5%. NH3 can induce the conversion of chloride to C–Cl, making it easier to bind to Hg 0 . NO also exhibits a promoting effect on mercury removal. This is because Hg 0 can be converted to HgO by the oxidation of NO. When the flue gas contains both NH3 and NO, the mercury removal efficiency is not as good as when the two gases are present alone. It is due to that NO will be consumed with NH3 at high temperatures and NO3 − will be generated on the surface of biochar and occupy the active site. SO2 inhibits mercury removal by modified biochar through competitive adsorption. Sulphates and sulphites are more likely to form on the surface of biochar in the case of the coexistence of NH3 and SO2 . The deposition of the chemical salt on the surface of the biochar causes the pores to be blocked and the active sites to be occupied, thereby deteriorating the efficiency of mercury removal. Graphical abstract: Image 1 Highlights: NH3 is beneficial for mercury removal from Cl2 plasma-modified biochar. NH3 promotes the conversion of Cl − to C–Cl to produce more chlorine active sites. The efficiency of mercury removal will be weakened when NH3 is added to NO. Sulphates and sulphites occupy the biochar in coexistence of NH3 and SO2 .